DESCRIPTION OF KNOWLEDGE ABOUT CHANGES IN THE MENTSTRUAL CYCLE IN INJECTING CONTRACEPTIVE ACCEPTORS IN PLOSO BUDEN VILLAGE, DEKET DISTRICT, LAMONGAN REGENCY - Fadliyah, Lailatul; Pradi, Priyanti Eka (Journal of Vocational Nursing, 2020)
Introduction: Injection contraception is one of the most common pregnancy prevention methods in Indonesia because it works effectively, is practical in use, is relatively cheap and safe. The results of an initial survey of 8 injectable contraceptive acceptors who experienced changes in the menstrual cycle of amenorrhoea and spotting in Ploso buden Village, Deket Subdistrict, Lamongan District, were found to be 75.00% which concerned the changes in the menstrual cycle. The purpose of this study is to find out the description of knowledge about changes in the menstrual cycle in injecting contraceptive acceptors in Ploso Buden Village, Deket District, Lamongan Regency. Methods: This study used a descriptive design, with a population of 97 people and a sample of 53 people. The sampling used is purposive sampling. Data collection with a closed questionnaire. Data processing and data analysis by editing, scoring, coding, tabulating and presented in the form of narration then drawing conclusions. Results: Based on the results of the study, the majority (54.7%) of injectable contraceptive acceptors were knowledgeable about changes in the menstrual cycle and amenorrhoea and spotting. Consulsion: The reference of this research to increase knowledge about changes in the menstrual cycle is the role of health workers is very important can provide counseling, distribute pamphlets and posters.